Language attitudes of foochow undergraduates towards English, Bahasa Malaysia, Mandarin and their vernacular - Teddy, Nelson. (Universiti Malaysia Sarawak, UNIMAS, 2009)
This study investigated the attitudes of the Foochow undergraduates towards the four language varieties in their linguistic repertoire across the cognitive, affective and behavioral components of attitude. Their attitudes towards these varieties were then explained in terms of their integrative and instrumental orientation. A survey was conducted on 184 Foochow undergraduates in Universiti Malaysia Sarawak by using a questionnaire. The findings from the survey revealed that the respondents have different attitudes towards the four varieties. The Foochow undergraduates had consistent and positive attitudes towards English, Mandarin, Foochow and Bilingualism (Mandarin and Foochow). However, their attitude towards Bahasa Malaysia is positive only in the cognitive aspect but not affective and behavioral-wise. In the respondents’ integrative orientation, Mandarin ranked the highest followed by Foochow, English and Bahasa Malaysia. In their instrumental orientation, English is the variety they perceived as having the highest instrumental value, followed by Mandarin, Bahasa Malaysia, and Foochow. The study also found that the cognitive component of attitude is not analogous with instrumental orientation. On the other hand, the affective component of attitude is analogous with integrative orientation. This study revealed that the Foochow undergraduates retained positive attitude towards their vernacular but a pattern of shift to Mandarin was evident. Their negative attitude towards Bahasa Malaysia in the affective and behavioral aspect revealed their low emotional attachment with the national language. Meanwhile, their highly positive attitude towards varieties perceived as having high instrumental value like English and Mandarin indicated that they are active language pragmatists. This study is useful as it indicates the Foochow community’s current thoughts, beliefs, desires and preferences for varieties around them, as well as to reveal the vitality status of their vernacular vis-à-vis standard varieties.